1996
DOI: 10.1021/jf9503974
|View full text |Cite
|
Sign up to set email alerts
|

Growth-Promoting Potential and Toxicity of Spermidine, a Polyamine and Biogenic Amine Found in Foods and Feedstuffs

Abstract: Experiments were conducted to determine the relative growth-promoting potential and toxicity of dietary spermidine, a biogenic amine and polyamine. Week-old chicks were fed purified diets containing 0.0, 0.2, 0.4, 0.6, 0.8, or 1.0% supplemental spermidine for 2 weeks. As little as 0.4% supplemental spermidine depressed growth and hepatic ornithine decarboxylase activity, while hepatic concentrations of putrescine, spermidine, and N 1-acetylspermidine increased. In a second experiment, 0.00, 0.05, 0.10, 0.20, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…It seems that the C5 diamine (cadaverine) is more toxic to living organisms than the C4 diamine (putrescine). The toxicity of an amine compound depends on its aliphatic chain length and the number of free amino groups as shown in bacteria and animals (Bachrach and Weinstein, 1970; Smith et al, 1996). Further study is needed to understand the exact mechanism of the toxicity of diamine to the cell.…”
Section: Resultsmentioning
confidence: 99%
“…It seems that the C5 diamine (cadaverine) is more toxic to living organisms than the C4 diamine (putrescine). The toxicity of an amine compound depends on its aliphatic chain length and the number of free amino groups as shown in bacteria and animals (Bachrach and Weinstein, 1970; Smith et al, 1996). Further study is needed to understand the exact mechanism of the toxicity of diamine to the cell.…”
Section: Resultsmentioning
confidence: 99%
“…1998). Sousadias and Smith (1995) and Smith, Mogridge and Sousadias (1996), however, observed that these positive effects decline with increasing molecular weight and cationic charge of the polyamine molecule. Some studies with rainbow trout Oncorhyncchus mykiss (Fairgrieve, Myers, Hardy & Dong 1994) and Atlantic salmon Salmo salar L. (Opstvedt et al .…”
Section: Discussionmentioning
confidence: 95%
“…The higher rate of mortality compared to inhibition of MMS suggests the limited effects observed for spermidine against C. savignyi likely result from general toxicity rather than inhibition of metamorphosis. Spermidine has been previously reported as toxic to week-old chicks at 40.6% of feed (Smith et al 1996) and to rats at 6.0 6 10 5 mg kg 71 (Til et al 1997). Additionally, spermidine is cytotoxic to E. coli at 700.0 mg ml 71 (Limsuwun and Jones 2000) and to baby hamster kidney cells at 1.7 mg ml 71 (Brunton et al 1991).…”
Section: Discussionmentioning
confidence: 98%